2020
DOI: 10.3390/jcs4020081
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chlorhexidine Loaded Halloysite Nanotube Based Experimental Resin Composite with Enhanced Physico-Mechanical and Biological Properties for Dental Applications

Abstract: Objective: The objective of this study was to explore the effect of Chlorhexidine-loaded Halloysite nanotubes (HNT/CHX) fillers (diverse mass fractions from 1 to 10 wt.%) on physicochemical, morphological and biological properties of newly developed experimental dental resin composite, in order to compare with the properties of composites composed of conventional glass fillers. Methods: The dental resin composites were prepared by incorporating various proportions of HNT/CHX. Six different groups of specimens:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The cytotoxic effect of chlorhexidine (1–10%) loaded into halloysite nanotube‐based resin composites was recently studied by Barot et al. [51], who found no cytotoxicity to NIH‐3T3 (mouse embryonal fibroblast) cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic effect of chlorhexidine (1–10%) loaded into halloysite nanotube‐based resin composites was recently studied by Barot et al. [51], who found no cytotoxicity to NIH‐3T3 (mouse embryonal fibroblast) cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study corroborate other studies that show that experimental resin blends can be promising for the development new dental composites. 12 13 14 15 16 27 However, further investigations should be conducted to clarify not only the durability of this type of resin blend, analyzing marginal adaptation and bond strength, but also get an interesting formulation for the dental practice. Another important factor is the inclusion of inorganic filler particles for evaluating the performance of IBOMA as reactive diluent monomer in dental resins.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Studies have been developed to evaluate physical and mechanical properties of resins blends. [10][11][12][13][14][15][16] The isobornyl methacrylate (IBOMA) is a monomethacrylate that has low viscosity and polymerization shrinkage. Studies show that their use in synthesizing nanogels for matrix resins aiming to reduce shrinkage and polymerization stress 15,16 is also used as comonomers thinners matrix composites because of their low viscosity, low polymerization shrinkage, and high hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recent studies on the release system have mainly been carried out to solve these problems. With the introduction of nanotechnology to either improve existing antibacterial materials or develop new antibacterial fillers, these problems have been resolved to a certain extent [ 30 , 31 , 32 ].…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…Experiments showed that they did not have any deleterious effects on the mechanical properties of the composite resin and there was a steady and slow release of copper particles even after 28 days. In addition, some nanocarrier agents for the delivery of drugs, such as montmorillonite and halloysite nanotubes were also used in dental resin composites to achieve controlled release of antibacterial agents [ 16 , 31 , 32 ].…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%